UNCLAIMED "DEMANDED PROFESSION" IN THE CAREERS OF LAW GRADUATES - Irina P. Popova (Moscow Polytechnic University, 2016)
The system of legal education has been developing to a greater extent under requirements of the market, going out of professionals' control. In the condition of uncontrolled growth the processes ofde ter ior ation of quality, under utilization of vocational education capacity and professional development take place. The study of this problem focuses on deformation of the careers of graduates with higher legal education, who have given up their specialty, and on the potential of this type of higher education to be the basis for transforming professional careers in other fields of activity. The research is based on the data of semi-structured interviews with graduates of law schools that do not work by a chosen profession. The circumstances of the choice of legal education and reasons of giving up the chosen profession are analyzed. It is also important to consider the resources of legal education for developing of professional careers in new areas.